Prevalence of mpox viral DNA in cutaneous specimens of monkeypox-infected patients: a systematic review and meta-analysis - Rani, Isha; Goyal, Anmol; Shamim, Muhammad Aaqib; Satapathy, Prakasini; Pal, Amit; Squitti, Rosanna; Goswami, Kalyan; Sah, Ranjit; Barboza, Joshuan J.; Padhi, Bijaya K. (Frontiers in Cellular and Infection Microbiology, 2023)
Background Human monkeypox (mpox) disease is multi-country outbreak driven by human-human transmission which has resulted in an International public health emergency. However, there is limited evidence on the positivity rate of skin lesions for mpox viral DNA. We aim to filling this gap by estimating the pooled positivity rate of skin samples with mpox viral DNA from mpox patients globally. Methods In this systematic review and meta-analysis, seven databases and several preprint servers have been extensively searched until 17 January 2023 according to a prospectively registered protocol (PROSPERO: CRD42023392505). Articles including the positivity rate of skin samples with mpox viral DNA in mpox confirmed patients were considered eligible. After a quality assessment, random-effects meta-analysis was used for pooled prevalence. To explore and resolve heterogeneity, we used statistical methods for outlier detection, influence analysis, and sensitivity analysis. Findings Amongst the 331 articles retrieved after deduplication, 14 studies were finally included. Pooled positivity rate of skin samples is 98.77% (95% CI: 94.74% - 99.72%). After removal of an influential outlier, I2 for heterogeneity dropped from 92.5% to 10.8%. Meta-regression did not reveal any significant moderator. Conclusion/Interpretation The present findings reinforce that skin lesions act as a reservoir of mpox viral DNA and contribute to a high infectivity risk. This may be a prevailing basis of prompt transmission during current multi-country outbreak and also needs further investigation. The present imperative outcome may benefit in producing valuable preventive and management procedures in appropriate health strategy. Keywords: Monkeypox, mpox viral DNA, skin lesion, cutaneous, meta-analysis, infectivity potential, transmission